Effect of molecular weight of curing agents on properties of nanocomposites based on epoxy resin and organoclay with reactive modifier - Jagtap, Siddheshwar B.; Ratna, Debdatta (Journal of Applied Polymer Science, 2017)
Nanocomposites of epoxy resin and clay modified with half neutralized salt of Jeffamine D400 were prepared by curing separately with three polyetheramines curing agents of different molecular weights and reactivity. The molecular weight of curing agents and their structural similarity with modifier played an important role in deciding the curing behavior, thermomechanical, and morphological properties of epoxy/clay nanocomposites. Morphological analysis carried out by X-ray diffraction (XRD) and transmission electron microscope (TEM) clearly show that the dispersion of clay layers in epoxy matrix decreases with decreasing molecular weight of the curing agents. Curing study done by using temperature modulated differential scanning calorimetry (MDSC) demonstrates that extragallery reaction rate increases with decreasing molecular weight of curing agents. Dynamic mechanical analysis (DMA) of epoxy/3 wt % modified clay composite prepared by curing with curing agent of higher molecular weight shows around 270% improvement in storage modulus (glassy) as compared with its neat epoxy network.